2020
DOI: 10.1186/s12914-020-00228-w
|View full text |Cite
|
Sign up to set email alerts
|

Community perspectives on the extent to which transactional sex is viewed as sexual exploitation in Central Uganda

Abstract: Background: Definitions of child sexual exploitation vary. Sexual exploitation violates children's rights and exposes them to mental and physical harm. There exist differences in views of behaviour that is considered exploitative, including transactional sex. This paper explores community perspectives on the extent to which transactional sex is considered exploitative. Methods: In 2014, we conducted 19 focus group discussions and 44 in-depth interviews with young people and adults in two communities in Uganda.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…There were also notable differences however, since participants in the Tanzanian study believed that transactional sex was exploitative when there was an imbalance of power based on age, economic capital, or social status. Research in Uganda similarly found that transactional sex was considered exploitative if it involved sex with a minor, misled a naïve or immature girl who lacked ability to give consent, or if there was a perceived power differential between the man and women/girl (Kyegombe et al, 2020). Our findings differ in this regard -there was little dialogue to suggest that exchanging sex with an underage girl was perceived as more exploitative or abusive than exchanging sex with an adult woman.…”
Section: Perceptions Around Justicecontrasting
confidence: 70%
“…There were also notable differences however, since participants in the Tanzanian study believed that transactional sex was exploitative when there was an imbalance of power based on age, economic capital, or social status. Research in Uganda similarly found that transactional sex was considered exploitative if it involved sex with a minor, misled a naïve or immature girl who lacked ability to give consent, or if there was a perceived power differential between the man and women/girl (Kyegombe et al, 2020). Our findings differ in this regard -there was little dialogue to suggest that exchanging sex with an underage girl was perceived as more exploitative or abusive than exchanging sex with an adult woman.…”
Section: Perceptions Around Justicecontrasting
confidence: 70%
“…This paper adds to a literature that goes beyond discussing the health impacts of engaging in transactional sex by interrogating motivations and emic (local) perspectives on transactional sex in Tanzania and Uganda (Kyegombe, Meiksin, Namakula, et al 2020;Wamoyi et al 2019;Wamoyi et al 2018). It informs the broader transactional sex literature, which tends to depict transactional sex in one of three broad paradigms (Stoebenau et al 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Transactional sex, defined as nonmarital, non-commercial sexual encounters or relationships primarily motivated by the implicit assumption that sex will be exchanged for material benefit or status (Stoebenau et al 2016), has been posited as one of the main drivers of girls' and young women's disproportionate risk of HIV infection owing to epidemiological evidence of a clear association (Ranganathan et al 2016;Dellar, Dlamini, and Karim 2015;Pettifor et al 2005;Rositch et al 2012;Wamoyi et al 2016;Choudhry et al 2015;Dunkle et al 2004;Jewkes et al 2012;Wamoyi et al 2011;Luke et al 2011). While transactional sex is not always considered by communities to be inherently exploitative, one situation in which transactional sex is viewed this way is when sex involves a minor or is considered to mislead a naïve or immature girl (Kyegombe et al 2020). Particularly in the context of Uganda's defilement laws, this raises questions about markers of transition from childhood to adulthood and when in this process young people are perceived by others to be appropriate subjects of sexual interest.…”
Section: Introductionmentioning
confidence: 99%